Post-activation performance enhancement strategies in sport: a brief review for practitioners - Daniel Boullosa (Termedia Publishing House, 2021)
In this review, we will present and critically discuss how different conditioning exercises can be implemented in training, testing, and competition for the enhancement of performances in different sports, via post-activation performance enhancement and other delayed potentiation responses. The potentiation approaches described here include warming up, testing and monitoring, re-warm-up and priming strategies, and complex training. The post-activation performance enhancement responses can be best described following the new taxonomy, which allows the identification of the best strategies in every specific sport setting. This requires identifying the post-activation performance enhancement factors, which are the conditioning activity, the verification test, the population of athletes; and potential moderators (i.e. exercise type and loading, timing; recovery interval, target exercise, performance parameter; training background, age, and sex). The inherent limitations to these approaches, including the gaps in literature requiring further studies, may be overcome in practice by using individualized approaches.